A survey on the impact of noise pollution from industrial activities to residential area / Norul Hayati Abas - Abas, Norul Hayati (Faculty of Architecture, Planning and Surveying, 2013)
Noise pollution can have a direct effect to the human health. Noise pollution has caused many people suffering if the noise level exceeds the limit of human hearing ears. Additionally, noise may interfere with the comfort of residential area. But nowadays, the residential was located near with the industrial activity. This factor will disturb the human comfort at the residential area. The objective of this dissertation is to identify the environmental issue due to industrial activity, to measure the sound level in the residential area and to examine the impact of noise pollution on neigbouring areas. This dissertation was use three method for data collected such as interviewing the related parties, distribute the questionnaire to local resident and measure the sound level meter at the residential area. The selected case studies for this dissertation are Taman Daya Maju and Taman Daya Meru which is located at Meru, Klang. In overall, both of residential area was receive a lot of noise. This is because; these residential areas located near with industrial and also located near to the main road. Through the case study, all data level was exceeding the noise levels that have set by the Environmental Department, which is 55dB. Based on data analysis that has been made, there are some issues that will be a source of building occupant discomfort which is caused by noise pollution. To reduce the noise pollution at these residential areas, the local authority or any related party can use the method such as construct the wall barrier, planting the trees around the residential area, enforcing the law and so on.